Prevalence and Molecular Characteristics of Polymyxin-Resistant Pseudomonas aeruginosa in a Chinese Tertiary Teaching Hospital - Chenlu Xiao; Yan Zhu; Zhitao Yang; Dake Shi; Yuxing Ni; Li Hua; Jian Li (Antibiotics, 2022)
Polymyxin-resistant Pseudomonas aeruginosa is a major threat to public health globally. We investigated the prevalence of polymyxin-resistant P. aeruginosa in a Chinese teaching hospital and determined the genetic and drug-resistant phenotypes of the resistant isolates. P. aeruginosa isolates identified by MALDI-TOF MS were collected across a 3-month period in Ruijin Hospital. Antimicrobial susceptibility was determined by a Vitek-2 Compact system with broth dilution used to determine polymyxin B (PMB) susceptibility. Polymyxin-resistant isolates were further characterized by molecular typing using PCR, multi-locus sequence typing (MLST) and whole-genome sequencing. Phylogenetic relationships were analyzed using single nucleotide polymorphism (SNP) from the whole-genome sequencing. Of 362 P. aeruginosa isolates collected, 8 (2.2%) isolates from separate patients across six wards were polymyxin-resistant (MIC range, PMB 4–16 μg/mL and colistin 4–≥16 μg/mL). Four patients received PMB treatments (intravenous, aerosolized and/or topical) and all patients survived to discharge. All polymyxin-resistant isolates were genetically related and were assigned to five different clades (Isolate 150 and Isolate 211 being the same ST823 type). Genetic variations V51I, Y345H, G68S and R155H in pmrB and L71R in pmrA were identified, which might confer polymyxin resistance in these isolates. Six of the polymyxin-resistant isolates showed reduced susceptibility to imipenem and meropenem (MIC range ≥ 16 μg/mL), while two of the eight isolates were resistant to ceftazidime. We revealed a low prevalence of polymyxin-resistant P. aeruginosa in a Chinese teaching hospital with most polymyxin-resistant isolates being multidrug-resistant. Therefore, effective infection control measures are urgently needed to prevent further spread of resistance to the last-line polymyxins.